2018
DOI: 10.1590/1809-6891v19e-28150
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento Ingestivo De Novilhos Mestiços Terminados Em Confinamento Alimentados Com Borra De Soja

Abstract: Resumo Este trabalho objetivou avaliar os efeitos da inclusão da borra de soja no comportamento ingestivo de 30 novilhos mestiços Charolês/Nelore, confinados, com 20 meses de idade e peso médio inicial de 328,3 kg. Cada grupo experimental foi composto por seis animais, distribuídos nos tratamentos: 00; 30; 60; 90 e 120 g de borra de soja por 1000 g de matéria seca na dieta, os quais continham 29,0; 47,3; 66,7; 86,8 e 106,8 g de extrato etéreo, respectivamente. O aumento no nível de inclusão de borra de soja na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
2
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 16 publications
0
5
2
2
Order By: Relevance
“…Animals fed diet containing soybean hulls and white oat grains had a lower total rumination time when compared to animals fed only soybean hulls or white oat grains. A correlation between rumination time and NDF content (r = −0.42; P = 0.02) was obtained by Callegaro et al (2018) when assessing soybean soapstock inclusion levels in the diet (0-12%), a result different from that obtained in this study. The authors attributed this correlation by the lack of physically effective fiber provided by the ingredient soybean hulls.…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…Animals fed diet containing soybean hulls and white oat grains had a lower total rumination time when compared to animals fed only soybean hulls or white oat grains. A correlation between rumination time and NDF content (r = −0.42; P = 0.02) was obtained by Callegaro et al (2018) when assessing soybean soapstock inclusion levels in the diet (0-12%), a result different from that obtained in this study. The authors attributed this correlation by the lack of physically effective fiber provided by the ingredient soybean hulls.…”
Section: Resultscontrasting
confidence: 99%
“…Throughout the day, animals fed diet mixture spent less time chewing food when compared to the diets with white oat grains and soybean hulls, which did not differ significantly from each other. Different from that obtained in this study, Callegaro et al (2018) stated that the higher the energy density of the diet and the lower the NDF content are, animals perform a lower number of chews per bolus and ruminate lower regurgitated bolus per day. Pereira et al (2007) studied the ingestive behavior at different levels of diet neutral detergent fiber and found that its increase from 30 to 60% increased the number of chews per bolus, the number of bolus per day and, consequently, the number of chews per day and the total chewing time.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations